Cloud computing in financial services - Nicoletti, Bernardo (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
This book analyses in depth the cloud computing model and its current and potential use in financial services.
Includes bibliographical references (pages 210-215) and index.
oif 12/06/15
Loan
Keywords: Banks and banking -- Information technology; Financial services industry -- Information technology; Cloud computing